2014
DOI: 10.7314/apjcp.2014.15.8.3613
|View full text |Cite
|
Sign up to set email alerts
|

Stathmin is a Marker of Progression and Poor Prognosis in Esophageal Carcinoma

Abstract: Stathmin, also called oncoprotein 18, is a founding member of the family of microtubule-destabilizing proteins that play a critical role in the regulation of mitosis. At the same time stathmin has been recognized as one of responsible factors in cancer cells. The aim of this study was to assess stathmin status, its correlations with clinicopathological parameters and its role as a progosnostic marker in EC patients. The protein and mRNA levels of stathmin were examined byimmunohistochemistry (IHC) and in situ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…Nie et al [19] found that increased STMN1 expression was observed non-small cell lung cancer, and high expression of STMN1 protein was tightly related to poor tumor differentiation, large tumor size, advanced N stage, and advanced TNM stage, implying STMN1 may play a critical role in the progression of NSCLC and may serve as a useful prognostic biomarker of the patients with NSCLC. In addition, Wang et al [18] demonstrated that significantly increased STMN1 protein expression was observed in were 73.0% in esophageal carcinoma tissues and 30.0% in the corresponding normal esophageal mucosa tissues, and further investigation found that increased STMN1 expression was significantly correlated with tumor differentiation, lymph node metastasis, TNM clinical classification and tumor invasion distant metastasis, suggesting that STMN1 might be essential in conferring a more aggressive behavior in esophageal carcinoma.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Nie et al [19] found that increased STMN1 expression was observed non-small cell lung cancer, and high expression of STMN1 protein was tightly related to poor tumor differentiation, large tumor size, advanced N stage, and advanced TNM stage, implying STMN1 may play a critical role in the progression of NSCLC and may serve as a useful prognostic biomarker of the patients with NSCLC. In addition, Wang et al [18] demonstrated that significantly increased STMN1 protein expression was observed in were 73.0% in esophageal carcinoma tissues and 30.0% in the corresponding normal esophageal mucosa tissues, and further investigation found that increased STMN1 expression was significantly correlated with tumor differentiation, lymph node metastasis, TNM clinical classification and tumor invasion distant metastasis, suggesting that STMN1 might be essential in conferring a more aggressive behavior in esophageal carcinoma.…”
Section: Discussionmentioning
confidence: 98%
“…Numerous studies have noted that the constitutive activation and overexpression of STMN1 were associated with a variety of human malignancies, including acute leukemia [12], nasopharyngeal carcinoma [13], hepatocellular carcinoma [14], gastric cancer [15], cervical carcinoma [16], colorectal cancer [17] and esophageal squamous cell carcinoma [18]. Nie et al [19] found that increased STMN1 expression was observed non-small cell lung cancer, and high expression of STMN1 protein was tightly related to poor tumor differentiation, large tumor size, advanced N stage, and advanced TNM stage, implying STMN1 may play a critical role in the progression of NSCLC and may serve as a useful prognostic biomarker of the patients with NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, we performed a series of subgroup analysis and found that stathmin displayed a higher expression in advanced cancers, poor differentiated cancers and cancers with lymphatic metastasis, which implied that stathmin intimately involved in tumor cell differentiation, proliferation and invasion of tumors. Metastasis and invasion are the critical factors in the progression of cancer, stathmin has been reported intimately correlating with malignant behavior of tumors [5, 8, 9, 22, 3841] and affect the survival of tumor patients. In our study, we noticed that patients who exhibited high expressions of stathmin had a significantly shorter post-surgical survival time (27.93 ± 11.54 months) compared with patients who exhibited moderate and low expressions of stathmin (44.81 ± 15.82 months).…”
Section: Discussionmentioning
confidence: 99%
“…At the molecular level, Stathmin 1 depolymerizes microtubules by either sequestering free tubulin dimers or directly inducing microtubule-catastrophe [31]. As mentioned before, Stathmin 1 is encoded by the human STMN1 gene, which has 4 serine phosphorylation sites.…”
Section: Discussionmentioning
confidence: 92%